Hubungan Video Pembelajaran dengan Motivasi Belajar Siswa Kelas V di SD Negeri 24 Macanang - Nurfadillah Nurfadillah; rukayah rukayah; sidrah afriani Rahman (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The problem in this study is that in the learning process the teacher is still dominated by using printed teaching materials in the form of student books and teacher books, therefore the need for several learning resources that can stimulate and increase student learning motivation, one of which is the use of learning videos. This research is a quantitative correlational study that aims to determine the relationship between video learning and the learning motivation of fifth grade students at SD Negeri 24 Macanang. The research data were obtained by distributing questionnaires to students. The results showed that there was a significant relationship between learning videos and students' learning motivation at SD Negeri 24 Macanang with a value of (3.6559) greater (>) value (1.67469) which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the learning video will have an impact on students' learning motivation. So the more often learning videos are used, it will increase students' learning motivation. From these conclusions, the impact resulting from this study is known that a good learning video will increase students' learning motivation